KEBERAGAMAN SISTEM KALENDER UMAT ISLAM PERSPEKTIF TEORI DIFERENSIASI SOSIAL HERBERT SPENCER - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2014)
Herbert Spencer’s theory of social difference states that societydynamically develops to adjust with environment. In relation tothe history of Islamic calendar, the development can be tracedback from the varieties of systems in calendar-making. Suchvarieties were resulted as Moslem societies must adjustment totheir new environment. Formerly, the decision of a new monthis done by a method named as rukyatul hilal. Then, as with thedevelopment of new methods, there come hisab method, kasyafmethod, and others.Kata kunci: Sistem Kalender, Teori Deferensiasi Sosial, HerbertSpencer